Debby Sahertian and Bahasa Gaul on YouTube Optimize Communication In The Digital Era. - Retika Niluh Alfala Putri; Dwi Prasetyo (LPPM Stikosa-AWS, 2023)
Communication is a form of conveying messages to the message recipients; it can flow smoothly if the recipients understand what is being conveyed. When communicating with her guest, Debby Sahertian uses slang, regardless of whether the guest can comprehend the slang or not. Researchers are interested in studying Debby Sahertian's use of slang to ensure smooth communication with her guests. The researchers aim to explore what communication style Debby Sahertian employs and want to gather the informants' opinions about Debby Sahertian's use of slang. This research is qualitative and employs a descriptive method. The researchers selected two videos from Debby Sahertian's YouTube channel as the research objects and posed questions to the informants. The research aims to uncover Debby Sahertian's communication style and how the informants perceive her use of slang, based on their individual opinions. The findings reveal that some informants have different views regarding Debby Sahertian's use of slang, and her communication style is described as assertive and passive.